UKRAINIAN CONTEXT OF PRESERVING JOURNALISTS’ MENTAL HEALTH: CHALLENGES OF FULL-SCALE WAR AND RESOURCES OF RESILIENCE - Yarkho, Olha (Personality and environmental issues, 2025)
The purpose of the work is to conduct a comprehensive theoretical and methodological analysis of specific challenges to the mental health of Ukrainian journalists in conditions of full-scale war; to identify and systematize a multi-level system of psychological resilience resources, including individual, professional, social, cultural, and existential components. Methodology. The research is based on systemic and integrative approaches to studying individual mental health in extreme conditions, cultural-historical approach to understanding resilience mechanisms, and phenomenological approach to comprehending the subjective experience of journalists. The theoretical foundation includes concepts of stress resistance and psychological adaptation (Mykola Korolchuk, Valentyna Korolchuk), theory of psychological support for extreme profile specialists (Serhii Myronets), neurobiological approach to trauma (Bessel van der Kolk), concepts of media-psychological safety (Liubov Naidonova) and information-psychological security (Oleh Baryshpolets). Methods of theoretical generalization, systemic and comparative analysis, content analysis, and phenomenological description were used. Scientific novelty lies in the systematization of unique characteristics of the Ukrainian context of preserving journalists' mental health; identification of a specific configuration of stressors (primary, secondary, and visual traumatization, information overload, identity conflict); substantiation of a multi-level system of psychological resilience resources; development of practical recommendations taking into account the specifics of wartime. Conclusions. It has been established that the specificity of the Ukrainian context is determined by the scale, duration, and hybrid nature of the conflict, which makes traditional mechanisms of psychological recovery impossible. A unique configuration of challenges and powerful resilience resources at individual, professional, social, and cultural levels has been identified. It has been proven that traumatic experience can become a catalyst for post-traumatic growth. Preserving journalists' mental health acquires strategic significance for the information security of the state.